Bacterial Identification And Antibiotics Sensitivity Of Ventilator-Associated Pneumonia (VAP) Patients At RSD Dr. Soebandi Jember - Shodikin, Muhammad Ali; Ramadhanty, Mira Haninda; Semita, I Nyoman (Universitas Nahdlatul Ulama Surabaya, 2021)
ABSTRACT Ventilator-Associated Pneumonia (VAP) is pneumonia in patients who use mechanical ventilator. The empirical antibiotic therapy is given to VAP patients based on bacterial mapping and its antibiotic sensitivity. The aim of this study is to determine bacterial identification and antibiotic sensitivity of VAP patients at RSD dr. Soebandi Jember. This study is a retrospective study, the data collected from medical record of VAP patients from September to October 2019. All samples that is meet the inclusion and exclusion criteria was recruited in this study. Data analysis was use Microsoft Excel 2010. This study obtained 15 samples. The most frequents bacteria that causes VAP is Acinetobacter baumanii. It is also caused by Klebsiella pneumoniae, Pseudomonas aeruginosa, Enterobacter aerogenes, Burkholderia cepacia, Pseudomonas fluorescence, Salmonella arizonae, and Escherichia coli. The bacteria are most sensitive to amikacin, meropenem, and piperacillin-tazobactam and most resistant to cefixime, cefotaxime, and ceftriaxone.